Music in Film and Literature through Shen Congwen’s Editing of the Script of The Border Town (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2014)
When editing the film script of his novella The Border Town, Shen Congwen gave special instructions not just on the storyline, but also on how sounds should be used in the film. This paper analyses the effect of the differentiated use of music and sound by the author and director.